Uma proposta de unidade didática multiestratégica para o ensino de princípios da espectroscopia em uma abordagem CTS - Oliveira, Evilim Martinez de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The teaching of spectroscopy, even though it is not part of the official school curricula, is very important for students to assimilate phenomena related to the constitution of the subject and confront this knowledge with the advances promoted by science. However, numerous research have shown that high school graduates have difficulties in formulating concepts related to problems at a microscopic level and that these difficulties may be related to the decontextualization to which this content is usually approached in the classroom. In this sense, this work aims to propose a lesson planning, which can be a useful tool to help in the organization and reflection on this content. The planning was proposed in the form of a Multistrategy Didactic Unit, which is elaborated from seven tasks, being them: (i) characterization of the school context, (ii) epistemological scientific analysis, (iii) didacticpedagogical analysis, (iv) methodological approach, (v) definition of objectives, (vi) definition of didactic strategies and (vii) definition of evaluation strategies. The Multistrategy Didatic Unit was based on the Science-Technology and Society (CTS) methodological approach.

O ensino de espectroscopia, mesmo não fazendo parte dos currículos escolares oficiais, é muito importante para que os alunos assimilem fenômenos relacionados à constituição da matéria e confronte esse conhecimento com os avanços promovidos pela ciência. Porém, inúmeras pesquisas têm mostrado que os estudantes egressos do ensino médio têm dificuldades em formular conceitos relacionados a problemas em nível microscópico e que essas dificuldades podem estar relacionadas com a descontextualização a qual esse conteúdo normalmente é abordado em sala de aula. Nesse sentido, este trabalho objetiva propor um planejamento didático-pedagógico, que pode ser uma ferramenta útil para auxiliar na organização e reflexão sobre esse conteúdo. O planejamento foi proposto na forma de uma Unidade Didática Multiestratégica, que é elaborada a partir de sete tarefas: (i) caracterização do contexto escolar, (ii) análise científico epistemológica, (iii) análise didático-pedagógica, (iv) abordagem metodológica, (v) definição dos objetivos, (vi) definição das estratégias didáticas e (vii) definição das estratégias avaliativas. A Unidade Didática Multiestratégica se baseou na abordagem metodológica Ciência-Tecnologia e Sociedade (CTS).
A proposal for a multistrategic didactic unit for the teaching of cts methodologic approach on spectroscopy's principles
Keywords: Unidades Didáticas Multiestratégicas; Espectroscopia; Modelos atômicos; CTS; Planejamento didático-pedagógico